Adsorption of bisphenol A on oil palm biomass activated carbon: characterization, isotherm, kinetic and thermodynamic studies - Kristanti, Risky Ayu; Hadibarata, Tony; Al Qahtani, Hamad M. S. (Biointerface Research, 2019)
Bispheol A (BPA) is one of the new emerging pollutants that frequently utilized in many industries. BPA is a chemical that indisputable can mimic human estrogen and disrupt the endocrine system. Thus, two low-cost adsorbents (oil palm trunk and palm shell) with various physicochemical parameters were analyzed for the removal of BPA. The most favorable pH for adsorption was found to be pH 3 (75% and 77%), the adsorbent dosage was 0.1 g (76% and 78%), while temperature was 25oC (76% and 78%) and agitation speed was 150 rpm (77% and 77%) for both oil palm trunk and palm shell. It was found that the best correlation with the experimental data of BPA adsorption was the Langmuir isotherm model, while the kinetic study could be well described with the pseudo-second-order model. The Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Brunauer–Emmett–Teller (BET) were carried out to understand the functional groups, morphology, and surface area of oil palm trunk and palm shell on adsorption of BPA.